Keterkaitan Antara Tranparansi Dengan Sifat Tabligh Dalam Penerapan Prinsip GCG (Studi Deskriptif Pada Perusahaan Distributor Makanan) - Adinda Ayu Nawangsari; Akhmad Kamaludin; Mohamad Djasuli (CV. ITTC INDONESIA, 2022)
The link between transparency and the nature of tabligh in the application of GCG principles to foodidistributor companies around the Jombang area. Researchers have a goal to find out the link betweenitransparency and the nature of tabligh in the application of GCG (Good Corporate Governance) principles.iThe results of this study indicate that in transparency with the nature of tabligh it is proven that it isiflexible in its flow and also the information obtained will be directly shared with the respective divisions ofithe company while in the policies made by the company, all these policies are determined by superiors,icommissioners and director where commissioners and directors make policies based on the interests of everyiemployee in the company. The policies made include policies regarding company regulations, companyioperational standards of each division, personnel policies, policies regarding promotion, and others. Theicompany has tried to convey and inform each existing policy properly and openly